2022
DOI: 10.1111/sode.12623
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between coping and peer victimization: Moderation by gender and initial peer victimization

Abstract: Stress coping theories suggest that the effectiveness of coping depends on the level of stress experienced. Existing research shows that efforts to cope with high levels of peer victimization may not prevent subsequent peer victimization. Additionally, associations between coping and peer victimization often differ between boys and girls. The present study included 242 participants (51% girls; 34% Black, 65% White; Mage = 15.75 years). Adolescents reported on coping with peer stress at age 16 and on overt and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Because preliminary analyses found gender differences in coping strategies, gender was included as a control. Overt and relational victimization were included because prior research has indicated each form of victimization is differentially related to different coping strategies (McWood et al., 2023), as well as for their significant correlations with adjustment outcomes and coping strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Because preliminary analyses found gender differences in coping strategies, gender was included as a control. Overt and relational victimization were included because prior research has indicated each form of victimization is differentially related to different coping strategies (McWood et al., 2023), as well as for their significant correlations with adjustment outcomes and coping strategies.…”
Section: Resultsmentioning
confidence: 99%